THE INFLUENCE OF ENTREPRENEURSHIP EDUCATION, FAMILY BUSINESS BACKGROUND, AND DESIRE FOR INDEPENDENCE ON IBA STUDENTS ENTREPRENEURIAL INTENTION - Manoppo, Deddy (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2013)
There are several motivations for people who would like to reach what they want to achieve. Some of the people say they want to become entrepreneurs because they can make money on their own and set their own rules. This research is to analyze the influence of Entrepreneurship Education, Family Business Background and Desire for Independence on students Entrepreneurial Intention. Entrepreneurship refers to conceiving an opportunity to offer new or improved goods or services, showing the initiative to pursue that opportunity, making plans, and mobilizing the resources necessary to convert the opportunity into reality. The sample used in this research is the students in 2nd to final year of the studies in International Business Administration, Faculty of Economics and Business, Sam Ratulangi University environment (students have already studied entrepreneurship) with family business background. The samples taken are 100 respondents. Entrepreneurship Education, Family Business Background and Desire for Independence have a strong relationship and significant influenceon Entrepreneurial Intention. It has proven by a significant level of this model prediction is above 95% which means that the probability of this model doing error is less than 5%, in other words, by hundred times of using this model, error will only occur less than 5 times. This research concluded that there is significant partial and simultaneous influence of Entrepreneurship Education, Family Business Background and Desire for Independence on IBA Program students Entrepreneurial Intention. Keywords: entrepreneurship education, family business, desire for independence, entrepreneurial intention